OPTIMIZATION OF HIGHER ORDER THINKING SKILLS (HOTS) IN ECONOMIC LEARNING AT SMKN 2 BLITAR - Ni’mah, Siti Rojabiyatun; Sugiono, Sugiono; Muchson, M. (Nusantara Economics and Entrepreneurships Journals, 2024)
With Higher Order Thinking Skills, a person can identify patterns, recognize underlying assumptions, and question the veracity of the information received. This allows individuals to develop a broader and deeper perspective, and produces more critical and reflective thinking. Higher Order Thinking Ability is not only related to intellectual intelligence, but also involves emotional and social aspects in exploring various points of view and understanding the complexity of human interactions. It enriches a person's ability to communicate effectively, resolve conflict, and collaborate in diverse environments. Individuals can formulate more critical, reflective, and holistic thinking, which can then assist them in communicating more effectively, better resolving conflict, and collaborating. Productively in diverse and complex environments. The aim of this research is to see the extent of the influence of cooperative group investigation, problem based learning and inquiry strategies on high level thinking abilities at SMKN 2 Blitar. This research was conducted by looking for respondents who had taken economics subjects. The research technique used is interview methods with students regarding group collaboration in teams and according to time, learning to ask questions, what work has been produced and teacher involvement in checking understanding, stimulating understanding, training abilities, and motivating students in interacting. In the aspect of high-level thinking abilities, see the extent to which ideas emerge from students, whether they can compare or make analogies in solving everyday problems. The research method uses statistical analysis and explanation using hypothesis testing. This research leads us to the conclusion that all variables have a partial and simultaneous influence on high-level thinking abilities. Students need to improve their thinking skills through several of the variables above